Urgensi Pendidikan Karakter Bagi Anak Usia Dini - prawinda, raras ayu; rahayu, yayuk hastining; shofwan, arif muzayin; nindiya, devi candra (Journal of Childhood Education, Development and Parenting, 2023)
Character education for early childhood is felt to be very important, because forming character values ​​for early childhood is like carving on stone which can last a long time. This descriptive qualitative research with literature study will discuss the urgency of character education for early childhood. The data analysis technique uses content analysis by sorting out data according to the objectives and research problems. This paper produces several things as follows. First, character education is very important for early childhood due to the following reasons, one of which is that early childhood has not been much affected by negative things from outside themselves or their environment. Second, the most appropriate implementation of character education for early childhood is through habituation. Habituation is a very appropriate method to do in early childhood education because the tendencies and instincts of children in teaching and habituation are very large compared to other ages. Third, the benefits of character education for early childhood can be divided into two, namely short-term and long-term. Short-term benefits, among others: children can know, distinguish various examples of good and bad behavior and the impact and consequences of doing so. While the long-term benefits, among others: become a character figure who has a balance of intellectual, emotional, and spiritual intelligence.